Plan de mejoramiento en el proceso de producción mediante la instrumentación de la BPM para la Asociación Agrilteb de la Tebaida Quindío (2015)
The Project called IMPROVEMENT PLAN IN THE PRODUCTION PROCESS WITH THE BPM INSTRUMENTATION FOR AGRILTEB FROM LA TEBAIDA QUINDIO* was developed with the collaboration of Vanessa Villada Narvaez and Viviana León Londoño** to get the degree of Business administrator. Through observation, test and information get it from partners. Seeking the growth of production area in the Agrilteb association which is dedicated in the production of dairy products through this improvement plan. It was realized during the implementation that the production processes were obsolete, without standardization, they didn’t fulfill the safety parameters, the staff wasn’t properly trained and the installation wasn’t the ideal. For these reasons it became necessary to apply good manufacturing practices (BPM) to guarantee the quality on the products. In addition, it was detected more shortcomings in the company that generate a negative impact, for instance, the lack of corporate governance who accomplish their duties correctly. They used to argue about their differences and they don’t value their own company. They are not able to focus their strength to help in the company growth. Also, the lack of investment in advertising that could inform and persuade the clients of Agrilteb has been a barrier for the company growth. To sum up, it is necessary for the improvement plan success that the production area, advertising area, Infrastructure area and corporate governance work together for the company growth.